DIRECT COMPARISON OF GLOBAL PRECIPITATION AND ATMOSPHERIC WATER VAPOR ISOTOPOLOGUE FROM SPACE AND MODEL - Samuel J Sutanto (JURNAL SUMBER DAYA AIR, 2012)
Stable isotopes in atmospheric water are important climatic tracers used to derive information on the moisture recycling, paleoclimate from ice cores, cloud physics, troposphere-stratosphere exchange, climate studies, hydrological cycle, etc. Some traditional methods to measure stable isotopes in the atmosphere are labor intensive and spatially limited. Nowadays, measurements of isotopes in the atmosphere are becoming visible using satellites to retrieve the data in one hand and using global climate models on the other hand. Therefore, this study has been carried out to compare the isotopes measurements using both the latest satellites measurements (SCIAMACHY and TES) and some global climate models (GissE, ECHAM, MUGCM) for direct comparison. The results from both satellites measurements and models simulations show that there are some isotope effects such as latitude effect, continental effect, and altitude effect. Interaction between surface and atmosphere can also be seen from the analysis. The stable isotopes comparison from satellites, models and ground observation is in a good agreement (-100 The tropics and -260 The polar regions). The discrepancy of isotope from precipitation and water vapor also agrees well (-60 to -75 in tropics). In addition, a slope analysis from a correlation of total precipitable water and isotope ratio shows that measurements near from the surface is following Rayleigh-type rainout process and measurements in the middle troposphere is influenced by a mixing process.